ASSESSMENT OF THE EFFICIENCY AND VOLATILITY OF THE STOCK MARKET OF UZBEKISTAN - KADIROVA, KHADICHA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article examines the essence, significance and role of the stock market in the development of the national economy. The current state of the domestic stock market and enterprises - domestic "blue chips" - are analyzed. The need for the development of the stock market, assessment of its efficiency and volatility based on modern techniques adapted to the national stock market are substantiated. For investors, such an assessment of the efficiency of the stock and bond markets creates the basis for optimizing the allocation of assets when building portfolio strategies, and for issuers it serves as the basis for building a strategy for issuing activities.